Upaya peningkatan pengetahuan dan pencegahan demam berdarah pada masyarakat kelurahan darma - Amin, Hadriyani; Safitri, Rusni (Yayasan Inspirasi El Burhani, 2024)
Introduction: Dengue hemorrhagic fever or abbreviated as DHF is an acute febrile disease caused by the dengue virus. This virus enters the human bloodstream through the bite of mosquitoes from the Aedes genus, for example Aedes aegypti or Aedes albopictus. This disease is characterized by high fever continuously for 2 to 7 days and is accompanied by bleeding and shock which, if not treated immediately, can cause death Objective: The aim of this Community Service is to increase public knowledge about dengue fever and its prevention in Darma Environmental Batu-batu Village. Method: Knowledge increasing activities regarding increasing knowledge and preventing dengue fever were carried out. On Thursday, May 27 2024, 10.00 WITA, the opening of community service activities with the theme